Colorimetric and Fluorometric Determination of Fluoride in Tetrahydrofuran and Dimethyl Sulfoxide Using a 4-Hydroxypyrene Probe - Yue Sun; Yunchen Long; Wenhao Sun; Yibo Zhang; Qianhui Tang; Chan Li; Sihua Li; Jing Nie (Journal of Analytical Methods in Chemistry)
F– ions (fluoride ions) are crucial in various chemical waste and environmental safety contexts. However, excessive fluoride exposure can pose a threat to human well-being. In this study, a simple 4-substituted pyrene derivative known as 4-hydroxypyrene (4-PyOH) was designed as a colorimetric probe for detecting F– through the formation of hydrogen bonds between F– and a hydroxyl group. The probe 4-PyOH exhibited exceptional sensitivity and selectivity towards F– ions and was successfully utilized as test strips for detecting F– ions in organic solvents. The detection limit reached an impressively low level of 3.06 × 10−7 M in the organic solvent. The recognition mechanism was confirmed through 1H NMR titration.